2017
DOI: 10.4236/ojcm.2017.71002
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Crushing of Polymer Matrix Composite Tubular Structures: Review

Abstract: The present paper reviews crushing process of fibre-reinforced polymer (FRPs) composites tubular structures. Working with anisotropic material requires consideration of specific parameter definition in order to tailor a well-engineered composite structure. These parameters include geometry design, strain rate sensitivity, material properties, laminate design, interlaminar fracture toughness and off-axis loading conditions which are reviewed in this paper to create a comprehensive data base for researchers, eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 124 publications
(120 reference statements)
0
19
0
Order By: Relevance
“…In previous studies [19] [24], the crushing behaviour of box composite sections were investigate based on their energy absorption capability. It was prevailing that at 10˚ the energy absorption was significantly increased, in contrast, [8] the author studied cylindrical GFRP composite section and concluded that the increase in lateral inclination angle causes a significant drop in energy absorption and this is due to the geometry differences of two studies. The experimental morphologies (see Figure 3) of axial and off-axis angle 5˚ illustrated bundle fracture and close to brittle failure mechanism, which is a combination of lamina bending and transverse shearing modes.…”
Section: Crushing Behaviour Of Composite Sections Under Axial and Offmentioning
confidence: 98%
See 1 more Smart Citation
“…In previous studies [19] [24], the crushing behaviour of box composite sections were investigate based on their energy absorption capability. It was prevailing that at 10˚ the energy absorption was significantly increased, in contrast, [8] the author studied cylindrical GFRP composite section and concluded that the increase in lateral inclination angle causes a significant drop in energy absorption and this is due to the geometry differences of two studies. The experimental morphologies (see Figure 3) of axial and off-axis angle 5˚ illustrated bundle fracture and close to brittle failure mechanism, which is a combination of lamina bending and transverse shearing modes.…”
Section: Crushing Behaviour Of Composite Sections Under Axial and Offmentioning
confidence: 98%
“…Different types of crashworthy components were studied in the past two decades including material systems, various geometrical shapes and various fabrication methods were developed and axially tested [8] [9]. Since during an impact event, the thin-walled structures undergo severe collapse failure and in oblique loading conditions, it could suffer from drastic energy absorption reduction.…”
Section: Introductionmentioning
confidence: 99%
“…Irrespective of the component of structures material, progressive crushing failure and stability during the compression loading are major in determining the higher level of energy absorption [12]. Thus, to achieve the above criteria, there is a consensus that the structural geometry is counting as a key parameter influencing the crashworthiness level of composite material [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…it was stated, improvement in crushing behavior and energy absorption are also sensitive to the length of tubes. Many authors [12,19] carried out laboratory works on the crashworthiness characteristics of circular and square cross-section composite tubes. Furthermore, the radial corrugation significantly affects the energy obtain of the composite structures [20].…”
Section: Introductionmentioning
confidence: 99%
“…The effective response of energy absorption of thin-walled composite tubular absorbers depends on the design of its sub-structure; and their stability is determined by lay-up, geometry, laminate design, and strain rate sensitivity and their progressive failure mechanism. The main factor affecting progress crushing of tubular structures is interlaminar and intralaminar fracture toughness [7].…”
Section: Introductionmentioning
confidence: 99%